PEDAGOGICAL COLLEGES IN NATIONAL EUROPEAN EDUCATION SYSTEMS THROUGH THE PRISM OF PROFESSIONAL HIGHER EDUCATION IN UKRAINE - Vintonyak, Oksana (European Science, 2024)
Colleges as a unique type of educational institution have undergone a long and complex path of historical formation, and at the beginning of the 21st century have become an important, distinctive component of the national education systems of most Europe